Efektivitas Metode Jarimatika dalam Meningkatkan Kemampuan Berhitung Perkalian Siswa - Khusnul Himmah; Jamal Makmur Asmani; Latifah Nuraini (Mafapress bekerja sama dengan Prodi PGMI Fakultas Tarbiyah IPMAFA Pati, 2021)
This study aims to determine the effectiveness of the Jarimatika method in improving the multiplication ability of grade III students of MI Manba'ul Huda Tunjungrejo for the 2019/2020 academic year. This study describes the application of the Jarimatika method to the third grade students of MI Manba'ul Huda and then analyzes the suitability of the theory with practice so that its effectiveness can be determined. Collecting data in this study used interview and documentation methods while data analysis used Milles and Huberman's model analysis, namely data reduction, data presentation, data verification. The results of this study indicate that the application of the Jarimatika method can improve students' numeracy skills. Students look active and happy when applying the Jarimatika method. The test results showed that the majority of students had good multiplication arithmetic skills. In addition, there are three criteria for the effectiveness of learning methods that must be met. First, the learning completeness of grade III students shows that the majority of students have exceeded the minimum completeness criteria. Second, there is an increase and a difference between initial understanding and after learning. Third, it can increase the interest and motivation of students who have difficulty calculating multiplication